The Concept of Environmentally Friendly Individual Mobility in the Future - Golubić, Jasna; Steiner, Sanja; Jelušić, Frane (Promet - Traffic&Transportation, 2012)
The European cities are faced today by the phenomenon ofexpanding everyday activities, affecting directly the traffic development.Physical expansion, the growing number of cars androad networks explain the increase in car utilisation in all typesof travelling in the range of 75 to 90%.Due to the adverse effects on the environment caused bysuch growing motorisation, the efforts are made in order to establishenvironmentally friendlier traffic. The paper considersthe concept of environmentally friendly individual trafficthrough MCC (Micro Compact Car) and MCC- mobility .systemwhich will provide its linking with other traffic participants,which may have a long-term positive influence on the quality ofurban life.